An Approach toward Successfully Restoring a Partially Resected Dentulous Mandible - Khanna, Gagan; Teja, VTT; S, Pradeep; Gupta, Lokendra (Journal of Orofacial Research, 2013)
Oral rehabilitation of patients with mandibular resection present challenges to maxillofacial prosthodontist. Segmental resection is associated with postoperative facial disfigurement and disability. So, surgeons try to preserve the continuity of mandible, whenever feasible by marginal resection. As the surgical reconstruction (by implants and grafts) is not always feasible in every patient, prosthodontic approach has to be considered to restore the esthetics and function. The manner in which the principles of removable partial denture are applied and interpreted must be modified because of altered anatomic and functional situation. This article describes the prosthetic management of a patient following partially resected dentulous mandible. Clinical relevance: Treatment of maxillofacial patient involves preoperative evaluation, clinical and radiographic examinations, diagnostic casts, which allow the prosthodontist to plan the treatment. Definitive treatment in the form of tooth-borne cast metal partial denture can be advocated in patients who underwent mandibular resection. Objectives: To appraise the reader about treatment plan, procedures involved in the design and fabrication of definitive prosthesis for rehabilitation of patients with resected mandible.